Entrenamiento en “Open Mindfuness: Un Estudio Piloto - Miró Barrachina, María Teresa; Ibáñez, Ignacio; Felipe, Isaura; García, Nieves M. (Revista de Psicoterapia, 2015)
The purpose of this study is to explore the effects of a mindfulness training program, "The Open Mindfulness Fundamental Training" (OMFT), on a non-clinical sample of 27 persons. On the one hand, it was intended to study pre-post intervention changes and, on the other hand, whether previous experience was modulating these changes. Results showed significant differences in several dimensions of interoceptive awareness: the ability to control attention regarding body sensations, the ability to regulate body tensions paying attention to embodied sensations, and the ability to trust that the body is safe and reliable. In addition, decentering skills improve significantly after training, as well as perception of the awareness level and attention to the present experience during a specific time in a given context. Previous experience in meditation was not related to participants improvement after the intervention, so all of them were equally benefited.